MENTORING PROGRAMME AND WORK PERFORMANCE OF MRSM TEACHERS IN KELANTAN - Wan Suhaila Wan Yaacob (Proceedings of The ICECRS, 2016)
Work performance is of the essence in any organization. In an educational institution, teachers’ work performance plays a significant role in making the goals of the institution are achieved. Underperforming teachers have been an issue in Maktab Rendah Sains MARA (MRSM) since its establishment. Based on some literature, mentoring programme has been suggested to improve work performance. MRSMs have been exposed to information on mentoring and its benefits yet the implementation is by far disappointing. Thus, this working paper focuses on mentoring programme and its relationship to the work performance of the teachers of MRSMs in the state of Kelantan. The finding of this working paper reveals that the mentoring programme (in any way it is implemented) has a relationship with the teachers’ work performance. The implication of this working paper is for MRSMs to implement mentoring programme in its effectiveness so that the problem of underperforming teachers could be reduced.